Association between nutritional status, daily nutrition delivery and clinical outcomes of critically ill adult patients admitted to the intensive care unit: a protocol for Isfahan multicentre prospective observational cohort ICU study (the Isfahan-ICU study) - Awat Feizi; Sabrina Schlesinger; Nafiseh Shokri-Mashhadi; Somayeh Rajaii; Milad Nasiri Jounaghani (BMJ Open)
Introduction There is currently limited information regarding the association between the modified Nutrition Risk in Critically Ill (mNUTRIC) score, nutrition delivery and clinical outcomes in critically ill patients admitted to the intensive care unit (ICU) section.Methods and analysis The Isfahan-ICU study is a multicentre, prospective observational cohort study that will be conducted on critically ill adults treated in the trauma or medical ICU sections of six hospitals to investigate whether clinical outcomes, including length of ICU stay and 30-day survival, vary by the mNUTRIC score at admission or the 7-day nutrition delivery. This paper outlines the Isfahan-ICU study protocol approved by the ethics committee of Isfahan University of Medical Sciences, Iran. Patient confidentiality is ensured, and study results will be shared at conferences and in medical papers.Ethics and dissemination This study protocol was reviewed and approved by the ethics committee of the Isfahan University of Medical Sciences, Isfahan, Iran (IR.MUI.RESEARCH.REC.1401.184). The patient’s identity will be considered confidential and will not be revealed or published under any circumstances; all provisions of laws governing personal data protection will be observed. Patient data recorded in the electronic survey will be documented pseudonymously using de-identified patient ID codes, and authorised staff at each participating site will have access to only their identifiable data. Results from the study will be disseminated at national and international conferences and in medical papers.Trial registration number Ethics committee of the Isfahan University of Medical Sciences, Isfahan, Iran (IR.MUI.RESEARCH.REC.1401.184).